Transfer Learning of Convolutional Neural Networks - Marta BISTROŃ; Mateusz SERGIEL; Artur MACIOŁEK; Błażej ZIELONKA; Zbigniew PIOTROWSKI (Communications of International Proceedings, 2022)
This paper briefly describes the development process, architecture, and learning principle of convolutional neural networks. An example training of a model trained from scratch and a model using transfer learning with a small dataset is presented. Using the examples presented, the idea and purpose of using transfer learning are explained, as well as its importance in counteracting overfitting.
Keywords: convolutional neural networks; neural networks; transfer learning; computer vision; image recognition